Strategies for Using Learning Media in Islamic Religious Education Subjects - Wahyudi Widodo (JTP - Jurnal Teknologi Pendidikan, 2024)
Islamic Religious Education (IRE) is an important subject for every student to learn. Islamic Education learning can be organized by utilizing various types of learning media, as has been implemented in Madrasah Tsanawiyah Miftahul Ulum Wonokoyo, East Java, where Islamic Education learning involves the use of print media and audio-visual media as learning tools. The purpose of this study is to examine the strategy of using learning media in IRE subjects at Madrasah Tsnawiyah Miftahul Ulum Wonokoyo. The research method used in this study is descriptive qualitative method. Data were collected through literature study, observation, and interviews with three Islamic teachers at the MTs. The collected data were analyzed through three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the management of the use of learning media in IRE subjects at Madrasah Tsanawiyah Miftahul Ulum Wonokoyo is still weak. This is caused by several factors, namely the lack of support from the madrasah for the procurement of IRE learning media and the lack of willingness of IRE teachers to improve their competence in the use of learning media. Efforts to improve the management of the use of learning media in IRE subjects at Madrasah Tsanawiyah Miftahul Ulum Wonokoyo require some management improvements in aspects such as the curriculum that can support the effective use of learning media, the role of teachers to improve their competence in the use of learning media, learning methods and learning media.